High-Stakes Testing The Impact of the LPATE on English Language Teachers in Hong Kong (Springer Singapore, 2018)
This book provides a detailed account of the origin, development, administration, revision and subsequent research findings on the benchmarking initiative from 1996-2016. It presents an overall assessment of the initiative's impact on major stakeholders, predictions regarding the way forward, and implications for other countries, especially in South East Asia. In addition, the book discusses what the larger global community can learn from Hong Kong's two-decade experience of conceptualizing and implementing minimum standard language requirements for teachers.